A role for risperidone in the treatment of communication disorder and comorbid mental health problems?. (25th November 2015) - Moreton, Adam; Imran, Shermin
Abstract : This case report describes the co-occurrence of a psychiatric disorder with a specific communication disorder in a teenage girl who presented to youth mental health services in crisis, posing a significant risk of harm to herself and others. Description of this case would be of interest to practitioners in youth mental health in relation to the assessment and treatment of young people with similar difficulties. We present the case of a 17-year-old girl previously admitted to an inpatient adolescent unit. Her diagnosis was reformulated 4 months into her second admission to include a specific communication disorder with both receptive and expressive difficulties, evident from her pragmatic use of language. She was started on risperidone in month eight; following this, a significant improvement was seen and the patient was discharged a month later. Prior to the start of risperidone, a referral had been made to low secure adolescent services for further assessment and advice on management, due to the patient's challenging presentation and poor engagement with treatment.